2020
DOI: 10.1542/peds.2019-1703
|View full text |Cite
|
Sign up to set email alerts
|

Car Seat Tolerance Screening for Late-Preterm Infants

Abstract: BACKGROUND: The belief that late-preterm infants have similar cardiorespiratory maturity to term infants has led many institutions to limit car seat tolerance screens (CSTSs) to those born early preterm. The objective of this study was to evaluate the incidence and predictors of CSTS failure, focusing on late-preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…7 And in a study evaluating latepreterm infants, researchers found that 21% of those who failed .1 CSTS from the NBN ultimately required NICU admission for significant hypoxia and that twothirds subsequently required supplemental oxygen for safe discharge. 20 It remains unclear whether CSTS failure unnecessarily prolongs inpatient admission or properly identifies infants at risk for unstable cardiorespiratory status before discharge, thereby preventing adverse postdischarge outcomes, which is why more research is needed.…”
Section: Provider Attitudesmentioning
confidence: 99%
“…7 And in a study evaluating latepreterm infants, researchers found that 21% of those who failed .1 CSTS from the NBN ultimately required NICU admission for significant hypoxia and that twothirds subsequently required supplemental oxygen for safe discharge. 20 It remains unclear whether CSTS failure unnecessarily prolongs inpatient admission or properly identifies infants at risk for unstable cardiorespiratory status before discharge, thereby preventing adverse postdischarge outcomes, which is why more research is needed.…”
Section: Provider Attitudesmentioning
confidence: 99%
“…(1) information related to car bed screening procedures; (2) constant adult observation of the infant while in the car bed; (3) ensuring that the infant is securely strapped into the car bed and the car bed is properly secured within the automobile; and (4) that a repeat CSTS be performed and passed before transitioning the infant to a traditional car seat. 11 When an infant fails the CSTS and is discharged in a car bed, child passenger safety experts recommend repeating the CSTS based on factors including infant age, resolution of symptoms, and evidence of neurobehavioral maturation.…”
mentioning
confidence: 99%
“…1 In the United States, an estimated 19,096 preterm infants (5%) fail the CSTS annually, as well as many full-term infants with complex respiratory and cardiac issues. 2,3 Infants who fail the CSTS are recommended for car bed travel, ambulance travel, or in some instances, hospitalization may be prolonged until they pass the CSTS. 1,[4][5][6][7][8][9][10][11] Physical characteristics of infants at risk for car seatrelated oxygen desaturation events include prematurity, underdeveloped neck muscles, poor head control resulting from the head being relatively large in proportion to body, low birth weight, change in breathing pattern during sleep, heart disease, lung disease, congenital heart disease, and neurological conditions.…”
mentioning
confidence: 99%
“…The article by Magnarelli et al 1 in this issue of Pediatrics highlights 3 major issues of importance to clinicians and families caring for infants born late preterm. One is the importance of determining cardiorespiratory stability, especially before being tested for car seat tolerance in preparation for discharge; the second is the importance of appropriate use of car safety seats at the time of hospital discharge; and the third is the value of having a hospital discharge policy in place.…”
mentioning
confidence: 99%
“…5 Use of the hospital policy will expedite having the child's own car safety seat available for the screen, implementation of the CSTS, and providing instruction for caregivers before discharge. Although the Magnarelli et al 1…”
mentioning
confidence: 99%